The Ties that burdens ; trial by publicity ; little miracles [videorecording] - Canlas, Ruben; Cantada, Candy; Lazaro, Cheche; Valdellon, Nessa (The Probe Team, 1995)
Deals with the Flor Contemplacion's execution in Singapore and how it affected diplomatic ties between Philippines and Singapore; the Calauan Mayor Antonio Sanchez's claim to his conviction as trial by publicity and the education of special children in Cupertino Center.